PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOTOR (Studi Kasus Pada Konsumen PT. Leo Utama Motor Batu Aji Batam) - Sarfudin S; Edwin Agung Wibowo (Universitas Riau Kepulauan, 2014)
This research aims at understanding the influance of service’s quality toward the motorcycle purchasing’s decision for customerat PT. Leo Utama Motor Leo Batu Aji Batam and for proving is there any correlation among of the variable which can sean from fenomenon happened by the existence as permanen distributor at PT. Leo Utama Motor.The data are collected by using questionaire at 100 permanent distributor the data analysis in this research uses SPSS version 20’ s help. Technique of data collection in quantitaif research which is used is descriptive analysis and infeencial analysis.This research produces that there is no positive influence and significance vaiable Reliability (X1) toward purchasing’s decision (Y), there is positive and significance effect of variable responsiveness (X2) on purchasing’s decisions (Y). There is a positive and significance effect of the variable Assurance (X3) on purchasing’s decisions (Y) There is a positive and significance effect Emphaty variable (X4) on purchasing’s decisions (Y). There is a positive and significance effect Tangible variable (X5) on purchasing’s decisios (Y).